O PROJOVEM E A AÇÃO COMUNITÁRIA: UMA ANÁLISE DA PARTICIPAÇÃO DOS EGRESSOS NA COMUNIDADE - Santos, Magnúcia Bezerra Soeiro dos (2011)
This work focuses on the impact of research Dimension Community Action developed at the National Youth Inclusion (ProJovem), held in São Luís - MA, covering the first two years of implementation, with the intention to examine the occurrence of changes in the lives of graduates in relation to social participation and performance in these communities. The methodology is guided from a qualitative perspective and uses the features of the evaluation of public policy. In that sense, for the composition of the frame theoretical and methodological the categories are detailed public policy, youth, community action and participation, from studies based on: Street, 1998; Silva, 2008; Novaes, 2005; Jacobi, 1983; Dayrell, 2007; Pereira, 2001; Souza, 1987; Bordenave, 1983; Gohn, 2001; Souza, 2008 and others. They are also used procedures, instruments and research techniques for gathering data and information, among which include the analysis of existing documentation on the ProJovem, interview with the former coordinator for Community Action and social workers who acted as social educators and semistructured interviews with the graduates. Thus, this research it is clear that there are several elements related to the actual format of the program that does not constrain the achievement of goals. Also the constant deprivation of actions performed by the students has turned away the possibility of social participation of most young people interviewed. However, changes are observed in relation to the perceptions of graduates about the importance of demonstrations and demands for the transformation of existing reality in communities, as young people can evaluate the impact of ProJovem and detach the necessity for other elements that may contribute to change social.